Headache, Cerebrospinal Fluid Leaks, and Pseudomeningoceles after Resection of Vestibular Schwannomas: Efficacy of Venous Sinus Stenting Suggests Cranial Venous Outflow Compromise as a Unifying Pathophysiological Mechanism - Higgins, J. Nicholas; Macfarlane, Robert; Axon, Patrick R.; Mannion, Richard A.; Tysome, James R.; Donnelly, Neil; Moffat, David A.; Pickard, John D. (Journal of Neurological Surgery Part B: Skull Base, 2019)
Background Regardless of the operative approach, headache, cerebrospinal fluid (CSF) leaks, and pseudomeningoceles remain disproportionately common problems after surgery for vestibular schwannomas and have a significant negative impact on quality of life and potential to return to full employment. Recent work has raised the possibility that these problems may, in part, be related to acquired obstruction of cranial venous outflow. This article explores this idea further with respect to a group of patients with severe and intractable symptoms.Objective The main objective of this article is to describe our experience diagnosing, investigating, and treating cranial venous outflow obstruction following translabyrinthine resection of vestibular schwannomas.Methods Retrospective review of all patients (n = 9) at our institution referred for sigmoid sinus stenting following translabyrinthine surgery.Results Headache resolved or improved after sigmoid stenting in all five patients in whom it was the primary symptom. CSF leak was the primary problem in two patients. In one, the leak was unchanged, but headache improved. In the other, the leak resolved, and headache improved. Two patients had symptomatic pseudomeningoceles and both resolvedConclusion Assuming a meticulous approach to wound closure, a CSF leak following surgery for vestibular schwannoma can be viewed as a pathological, but essentially homeostatic, response to raised intracranial pressure caused by acquired obstruction to cranial venous outflow. Postoperative headache (from high or low intracranial pressure) and CSF leaks, therefore, may all respond to measures aimed at eliminating the obstructing lesion.
Keywords: vestibular schwannoma; sigmoid sinus stenting; headache; cerebrospinal fluid leak; pseudomeningocele; cerebral venous outflow obstruction